Rediscovery of the tree snail Bulimus appressus von Martens, 1867, with Bulimus perversus tener von Martens, 1867 placed as subspecies of Amphidromus palaceus (Mousson, 1848) (Gastropoda: Camaenidae) - Bunjamin Dharma; Irwan Wipranata (Masyarakat Moluska Indonesia, 2023)
Bulimus appressus von Martens, 1867 was described without shell image with the type locality